Marriage Law Reform in Indonesia A Maqasid al-Usrah Perspective on Legal Adaptation - Busriyanti, Busriyanti; Pujiono, Pujiono; Mursalim; Chamdan, Umar (Institut Agama Islam Negeri Curup, 2025)
This study explores the reform of Indonesian marriage law through the lens of maqasid al-usrah, the family-centered objectives within Islamic legal theory. It critically assesses whether key legal reforms such as marriage registration, minimum age requirements, regulation of divorce, and prenuptial asset arrangements align with the ethical aims of Islamic family law, including the protection of lineage, dignity, justice, and family welfare. Employing a qualitative library research method, the paper draws on classical Islamic jurisprudence, statutory legal documents, court practices, and the analytical framework of Jamaluddin al-Athiyya. It finds that while Indonesian legislation increasingly incorporates maslahah (public benefit) and maqasid reasoning to justify reforms, the implementation often falls short due to bureaucratic barriers, legal pluralism, and social inequality. For instance, minimum age laws are undermined by widespread judicial dispensations, and formal protections for women are diluted by enduring patriarchal norms and unequal access to justice. The study argues that maqasid al-usrah has been invoked more as a justificatory narrative than as a fully operational legal method. It concludes that meaningful application of maqasid requires not only legal reform but also structural, procedural, and cultural transformation to ensure that laws genuinely promote justice, protect the vulnerable, and reflect the dynamic needs of Indonesian Muslim society. This research contributes to the growing discourse on maqasid-based legal reform and offers a practical framework for evaluating future policy developments in Islamic family law.